2009
DOI: 10.1177/112067210901900404
|View full text |Cite
|
Sign up to set email alerts
|

Topographically Guided Two-Step LASIK and Standard LASIK in the Correction of Refractive Errors after Penetrating Keratoplasty

Abstract: After a long follow-up period, both topographically guided two-step LASIK and standard LASIK could be considered effective and safe tools in the correction of refractive errors after successful PKP for keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Studies have not reported significant differences in refractive and visual outcomes between LASIK and PRK [92,93]. The precision of FS-laser flap and custom [topography or wavefront guided (WFG)] ablation has improved LASIK outcomes [51,52 & ,87 && ,94]. We reported better astigmatic outcome using the twostep procedure [45] that was also reported by others [46,51,95].…”
Section: Outcomes Of Refractive Surgery In Corneal Graftssupporting
confidence: 81%
See 1 more Smart Citation
“…Studies have not reported significant differences in refractive and visual outcomes between LASIK and PRK [92,93]. The precision of FS-laser flap and custom [topography or wavefront guided (WFG)] ablation has improved LASIK outcomes [51,52 & ,87 && ,94]. We reported better astigmatic outcome using the twostep procedure [45] that was also reported by others [46,51,95].…”
Section: Outcomes Of Refractive Surgery In Corneal Graftssupporting
confidence: 81%
“…The precision of FS-laser flap and custom [topography or wavefront guided (WFG)] ablation has improved LASIK outcomes [51,52 & ,87 && ,94]. We reported better astigmatic outcome using the twostep procedure [45] that was also reported by others [46,51,95]. The difficulties in LASIK include challenging preoperative evaluation, irregular corneal surface, previous AK cuts, corneal biomechanics change and inadequate stromal thickness for full HOA correction [48,52 & ,96,97].…”
Section: Outcomes Of Refractive Surgery In Corneal Graftssupporting
confidence: 65%
“…However, no significant advantage of topography-guided LASIK over conventional LASIK has been reported. [15]…”
Section: Discussionmentioning
confidence: 99%
“…The presence of irregular anterior surfaces, often associated with large amounts of higher order aberrations, limits best spectacle-corrected visual acuity and visual quality. Among the various techniques proposed for correcting post keratoplasty astigmatism, laser-assisted in situ keratomileusis (LASIK) has been more encouraging, leading to greater reduction in preoperative astigmatism 2,3. The major disadvantages of LASIK are related to the creation of the lamellar flap.…”
Section: Introductionmentioning
confidence: 99%